Thyroxine transfer from cerebrospinal fluid into choroid plexus and brain is affected by brefeldin A, low sodium, BCH, and phloretin, in ventriculo-cisternal perfused rabbits - Zibara, Kazem; El-Zein, Ali; Joumaa, Wissam; El-Sayyad, Mohammad; Mondello, Stefania; Kassem, Nouhad (Frontiers in Cell and Developmental Biology, 2015)
Background: Thyroxine (T4) hormone is synthesized by the thyroid gland and then released into the systemic circulation where it binds to a number of proteins. Dysfunction in T4 transport mechanisms has been demonstrated in multiple central nervous system (CNS) diseases including Alzheimer's disease. In the presence of different compounds that inhibit potential T4 transport mechanisms, this study investigated the transfer of T4 from cerebrospinal fluid (CSF) into Choroid Plexus (CP) and other brain tissues. The compounds used were brefeldin A, low sodium artificial CSF (aCSF), BCH, phloretin, and taurocholate (TA). Methods: Radiolabeled T4 (125I-T4) was perfused continuously into the CSF and was assessed in several brain compartments with reference molecule 14C-mannitol and blue dextran, using the in vivo ventriculo-cisternal perfusion (V-C) technique in the rabbit. The aCSF containing the drug of interest was infused after 1 h of perfusion. Drugs were applied independently to the aCSF after 1 h of control perfusion. Results: Of interest, in presence of low sodium or BCH, the percentage recovery of 125I-T4, was increased compared to controls, with concomitant increase in T4 clearance. Conversely, brefeldin A, phloretin, and TA did not exert any significant effect on the recovery and clearance of 125I-T4 assessed in aCSF. On the other hand, the uptake of 125I-T4 into CP was raised by 18 fold compared to controls in the presence of brefeldin A. In addition, low sodium, BCH, or phloretin alone, enhanced the uptake of 125I-T4 by almost 3-fold, whereas TA did not show any significant effect. Finally, the uptake and distribution of 125I-T4 into other brain regions including ependymal region (ER) and caudate putamen (CAP) were significantly higher than in controls. Conclusion: Our study suggests the involvement of different mechanisms for the transfer of 125I-T4 from CSF into CP and other brain regions. This transfer may implicate sodium-dependent mechanisms, amino acid “L” system, or organic anion transporting polypeptide (OATP).